Inherited pancreatic exocrine insufficiency and pancreatitis: When children transition to adult care. (February 2022) - Scheers, Isabelle
Abstract: Hereditary pancreatitis (HP) encompasses two distinct disease groups: the first manifests as congenital exocrine pancreatic insufficiency (EPI), and the second includes hereditary forms of pancreatitis. EPI represents the ultimate expression of gland function loss. Cystic fibrosis is by far the most frequent aetiology of early-onset EPI; genetics and a growing understanding of the disease mechanisms have paved the way for innovative and personalized treatment approaches. Efforts are ongoing to further decipher the pathophysiology and explore new therapies for other causes of EPI. HP occurs in patients carrying mutations in genes encoding digestive proteases or proteins playing an important role in proper pancreatic function and homeostasis. Improved sequencing techniques have led to the discovery of several causal and disease promoting genes. Most forms of HP have a paediatric onset but complications usually manifest during adulthood. Surveillance in experienced centres is mandatory to diagnose and address these complications in a timely manner.